Pendidikan Karakter Melalui Pembelajaran Matematika Di Sekolah Dasar - Iwan Usma Wardani (Lembaga Bale Literasi, 2025)
Growing character education in elementary schools can be done through integration in learning. Even mathematics subjects that are considered as subjects that dwell on counting can integrate the content of character education. This study aims to determine the management of character education through mathematics learning in elementary schools including lesson planning, implementation of learning and evaluation of mathematics learning. The method used is qualitative with the type of library research with the object of research explored th rough various library information. The data analysis technique used is interactive data analysis using the Milles and Huberman model. The results showed that 1) The management of character education through mathematics learning includes program design and lesson plans covering character education in important skills and basic skills, and has a student character evaluation card. The character values listed in the curriculum and lesson plans include religion, honesty, discipline, democracy, creativity, curiosity, tolerance, social care, communication, and responsibility. 2) The management of character education in the preliminary activities of learning mathematics is for the teacher to get used to the application of religion, discipline, methods and environmental care. 3) Management of character education in the evaluation of mathematics learning, the teacher conducts an assessment by conducting daily tests and observing the attitudes, knowledge and skills of students in the learning process. Assessment or ev aluation of learning carried out in the learning process and tests can be done by observing social and religious attitudes, knowledge and skills of students.